2014
DOI: 10.1523/jneurosci.3620-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hilar Mossy Cells Provide the First Glutamatergic Synapses to Adult-Born Dentate Granule Cells

Abstract: Adult-generated granule cells (GCs) in the dentate gyrus must establish synapses with preexisting neurons to participate in network activity. To determine the source of early glutamatergic synapses on newborn GCs in adult mice, we examined synaptic currents at the developmental stage when NMDA receptor-mediated silent synapses are first established. We show that hilar mossy cells provide initial glutamatergic synapses as well as disynaptic GABAergic input to adult-generated dentate GCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 37 publications
4
83
0
Order By: Relevance
“…Notably, long-range serotonergic axons from the raphe arborize in the SVZ neurogenic niche and regulate the birth of new neurons (71). Other inputs to the inner ML emanate from commissural fibers or hilar mossy cells (72)(73)(74), which provide the first glutamatergic synapses onto newborn neurons of the dentate gyrus (75). Cell-specific stimulation of these neurons may help determine their action on the regulation of adult neuronal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, long-range serotonergic axons from the raphe arborize in the SVZ neurogenic niche and regulate the birth of new neurons (71). Other inputs to the inner ML emanate from commissural fibers or hilar mossy cells (72)(73)(74), which provide the first glutamatergic synapses onto newborn neurons of the dentate gyrus (75). Cell-specific stimulation of these neurons may help determine their action on the regulation of adult neuronal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hilar mossy cell and GABA interneuron, immature, and mature newborn granule neuron are marked with calretinin and GAD67, DCX, and NeuN, respectively. In the early stage and the indirect pathway, hilar glutamatergic mossy cells input excitatory action on GABA interneurons (53). The latter exerts initially excitatory actions on immature neurons, which are depolarized by GABA due to high expression levels of the chloride importer NKCC1 (Na ϩ /K ϩ /2Cl Ϫ co-transporter), to activate phosphorylated CREB (p-CREB) signaling pathway (54) and thus to promote early maturation of newborn neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We have also showed that methamphetamine treatment significantly enhanced neurogenesis of granule neurons in the hippocampus following severe TBI (Rau et al, 2012). Recent evidence indicates that mossy cells are the first glutamatergic neurons to make contact with newborn granule neurons (Chancey et al, 2014). Mossy cells also provide considerable feed forward inhibition onto granule neurons via parvalbumin (PV) and somatostatin (SST) positive inhibitory interneurons.…”
Section: Impact Of Amphetamines On Cognition and Neurogenesismentioning
confidence: 78%